Pengaruh Limbah Ampas Kopi sebagai Pupuk Organik Cair (POC) pada Pertumbuhan Bibit Kopi Robusta Propelegetim BP 42 X BP 358 di Main Nursery - Hartari, Widia Rini; Same, Made; Rahmawati, Dewi; Kusumastuty, Any (JURNAL AGROTROPIKA, 2024)
Coffee drink is a drink extracted from coffee beans that produces spent coffee grounds, which have macro chemical compounds for plants in terms of growth and development, namely Ca, Mg and N, P, K. The purpose of this study was to obtain the best dose of liquid organic fertilizer (LOF) from spent coffee grounds for the growth of coffee seedlings. The study was conducted from January to June 2023 at the Lampung State Polytechnic Practice Park, Bandar Lampung. This study used a Randomized Block Design, consisting of 4 doses of liquid organic fertilizer treatment (P0 = 0, P1 = 50 ml, P2 = 100 ml and P3 = 150 ml per polybag) with the observed variables being plant height, number of leaves, stem diameter and dry root weight at 14 to 84 days after planting (DAF). The results of this study are that the application of LOF from spent coffee grounds affects the height of coffee seedlings at 14 and 28 DAF, the number of leaves at 84 DAF, and the diameter of the stem at the age of 56, 70, 84 DAF, but does not affect the dry root weight. The best treatment is the application of LOF with a dose of 100 ml/polybag which has a major effect on plant height, number of leaves and stem diameter. Keywords: dregs, dose, spent coffee, liquid fertilizer